2023
DOI: 10.3390/ani13193010
|View full text |Cite
|
Sign up to set email alerts
|

Can the Inclusion of a Vegetable Biocholine Additive in Pig Feed Contaminated with Aflatoxin Reduce Toxicological Impacts on Animal Health and Performance?

Vanessa Dazuk,
Lara Tarasconi,
Vitor Luiz Molosse
et al.

Abstract: (1) Background: This study’s objective was to determine whether adding vegetable biocholine (VB) to pigs’ diets would minimize the negative effects caused by daily aflatoxin (B1 + B2) intake. (2) Methods: We used seventy-two whole male pigs weaned at an average of 26 days and divided them into four groups with six replicates each (2 × 2 factorial). The treatments were identified as Afla0VB0 (negative control, without aflatoxin and without VB); Afla500VB0 (positive control, 500 µg/kg of aflatoxins; Afla0VB800 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Some secondary metabolites found in BioCholine have antimicrobial effects [ 19 , 20 , 63 ] that may give it resistance to ruminal degradation of choline conjugates. Mendoza et al [ 19 ] analyzed the volatile compounds of the mixture by flash gas chromatography electronic nose.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some secondary metabolites found in BioCholine have antimicrobial effects [ 19 , 20 , 63 ] that may give it resistance to ruminal degradation of choline conjugates. Mendoza et al [ 19 ] analyzed the volatile compounds of the mixture by flash gas chromatography electronic nose.…”
Section: Resultsmentioning
confidence: 99%
“…The supplier of the polyherbal reports content of choline conjugates between 1.76 and 1.8%, a higher value than that reported by Leal et al [ 43 ] of 0.978% analyzed with High-performance Thin Layer Chromatography, with total phospholipids of 1.68%. Dazuk et al [ 63 ], using high-performance thin-layer chromatography, reported phosphatidylethanolamine, phosphatidylinositol, phosphatidylcholine, lysophosphatidylcholine, and 16.1% PTCho natural choline conjugates. The polyherbal has other metabolites that can affect the rumen microbiota and the metabolism of ruminants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional screen identified an inhibitor to BACH1, called 1-Piperazineethanol, α-[(1,3-benzodioxol-5-yloxy)methyl]-4-(2-methoxyphenyl) (M2), whose administration improved weight loss and liver injury in vivo in pigs [44]. The hepato-protective potential of another beneficial substance was confirmed when vegetable choline was added to counteract AFB1 in pig feed to alleviate liver damage at a dose of 800 mg/kg applied to the feed base mix [45].…”
Section: Afb1 Prevalence Detection and Treatment Of The Afb1 Animal M...mentioning
confidence: 99%